Hard choices : how women decide about work, career and motherhood - Gerson, Kathleen (California series on social choice and political economy., 1986)
How do women choose between work and family commitments? And what are the causes, limits, and consequences of the ""subtle revolution"" in women's choices over the 1960s and 1970s? To answer these questions, Kathleen Gerson analyzes the experiences of a carefully selected group of middle-class and working-class women who were young adults in the 1970s. Their informative life histories reveal the emerging social forces in American society that have led today's women to face several difficult choices.